PENGARUH PENERAPAN CORPORATE GOVERNANCE DAN UKURAN PERUSAHAAN TERHADAP CAPITAL STRUCTURE PERUSAHAAN MULTIFINANCE YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) TAHUN 2015-2018 - Regina Rahmadella, - (2021)
The purpose of this study is to see how much influence the implementation of good corporate governance and company size has on debt acceptance of multi-finance companies. Amount of company debt is seen in the analysis of the company's capital structure. Implementation of good corporate governance is one aspect that is considered by creditors and stakeholders because corporate governance is a series of mechanisms that direct and control the company so that the company's operations run in accordance with the expectations of creditors and stakeholders. Corporate governance used in this study is board of directors meetings, board of directors size and board of commissioners size. This research was conducted using data from companies listed in Indonesian Stock Exchange (BEI) for the 2015-2018 period. The sampling method in this study was purposive sampling the amount of samples are 44 samples. Hypothesis testing is done using multiple regression analysis. The results of this study indicate that board size and company size have a positive effect on the capital structure of multifinance companies. While the other variabel such board meetings and board of directors size, there was no positive influence on the capital structure of multifinance companies. Keywords: corporate governance, board of directors, board of commissioners, company size, capital structure, multifinance companies